Pharmacokinetics and Bioequivalence Evaluation of Two Acipimox Tablets: A Single-Dose, Randomized-Sequence, Two-Way Crossover Study in Healthy Chinese Male Volunteers - Huang, J.; Chen, R.; Wei, C.; Li, R.; Yuan, G.; Liu, X.; Wang, B.; Guo, R. (Drug Research, 2013)
The study was designed to compare the pharmacokinetic parameters and relative bioavailability of a newly generic acipimox 250-mg tablets (test formulation) with a branded 250-mg tablets (reference formulation).A single-dose, randomized-sequence, 2-way crossover study was conducted in 20 healthy Chinese male volunteers in the fasted state. Plasma samples were collected over 12 h after a single oral dose of 250-mg acipimox test or reference, followed by a 7-day washout period. Plasma concentrations of acipimox were analyzed by high-performance liquid chromatography. Drug And Statistical-Version 2.0 was used to calculate the pharmacokinetic parameters and assess bioequivalence of the 2 formulations. It is considered bioequivalent if the 90% CIs of the mean ratios (test: reference) for Cmax, AUC0–t and AUC0–∞ are all within the range from 80% to 125%.No period, formulation, or sequence effects were observed on any pharmacokinetic parameters. The main pharmacokinetic parameters for the test and reference were as follows: t1/2 were 1.412±0.168 h and 1.390±0.162 h; Tmax were 1.850±0.462 h and 1.800±0.571 h; Cmax were 4.035±1.055 μg · ml-1 and 3.858±0.986 μg · ml-1; AUC0–12 were 14.006±2.564 μg · ml-1 · h and 13.345±2.128 μg · ml-1 · h, and the AUC0–∞ were 14.147±2.568 μg · ml-1 · h and 13.486±2.117 μg · ml-1 · h. The 90% CIs for the ratios (test/reference) of Cmax, AUC0–12, and AUC0 − ∞ were 98.0–111.2%, 100.8–108.5%, and 100.8–108.3%, respectively.In this small study, a single 250-mg oral dose of an acipimox tablet (test formulation) is bioequivalent to the established reference formulation.
Keywords: determination; acipimox; HPLC